2014
DOI: 10.1007/s11103-014-0260-3
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Overexpression of a cotton annexin gene, GhAnn1, enhances drought and salt stress tolerance in transgenic cotton

Abstract: Plant annexins are members of a diverse, multigene protein family that has been associated with a variety of cellular processes and responses to abiotic stresses. GhAnn1, which encodes a putative annexin protein, was isolated from a cotton (Gossypium hirsutum L. acc 7235) cDNA library. Tissue-specific expression showed that GhAnn1 is expressed at differential levels in all tissues examined and strongly induced by various phytohormones and abiotic stress. In vivo and in vitro subcellular localization suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 90 publications
2
31
0
Order By: Relevance
“…Recently, it was shown that GhCaM7 promotes early cotton fiber elongation by modulating ROS production (Tang et al, 2014b). Most importantly, it has been demonstrated that AnnAt1, AnnBj1, and GhAnn1 affect root growth associated with H 2 O 2 (Divya et al, 2010;Richards et al, 2014;Zhang et al, 2015a). Consistent with these findings, we found that exogenous H 2 O 2 promotes fiber elongation at concentrations lower than 20 mM (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Recently, it was shown that GhCaM7 promotes early cotton fiber elongation by modulating ROS production (Tang et al, 2014b). Most importantly, it has been demonstrated that AnnAt1, AnnBj1, and GhAnn1 affect root growth associated with H 2 O 2 (Divya et al, 2010;Richards et al, 2014;Zhang et al, 2015a). Consistent with these findings, we found that exogenous H 2 O 2 promotes fiber elongation at concentrations lower than 20 mM (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, annexins also were found to participate in cell elongation. Transgenic cotton seedlings overexpressing AnnBj1 and GhAnn1 both showed welldeveloped root systems with significantly enhanced root length under salt and drought stress (Divya et al, 2010;Zhang et al, 2015a). AnnGh3, which is preferentially expressed in fibers, promotes the initiation and elongation of leaf trichomes (Li et al, 2013b).…”
mentioning
confidence: 99%
“…Transgenic cotton for drought tolerance has increased OA capability, relative water content, photosynthesis, and lower ion leakage percentage. The expression of mustard annexin gene (AnnBj1) was shown to increase stress tolerance in cotton with higher sucrose and proline contents [84,85], whereas overexpression of the cotton GhAnn1 annexin gene increased the action of SOD, proline, and soluble sugars for drought and salt tolerance [86].…”
Section: Morpho-physiological Responsesmentioning
confidence: 99%
“…However, by far the greatest percentage of transgenic cotton is aimed at controlling insect pest damage in the form of the expression of various forms of insecticidal proteins from Bacillus thuringiensis (i.e., Bt cotton). Recently, several genes have been used to improve the drought tolerance of transgenic cotton, including AtLOS5, encoding a molybdenum cofactor sulfurase responsible for aldehyde oxidase activity; GhAnn1, an annexin gene; isopentenyl transferase (IPT), a rate-limiting enzyme for cytokinin biosynthesis; and 14-3-3 genes that regulate the activity of plasma membrane H + -ATPase (Yan et al, 2004;Yue et al, 2012;Kuppu et al, 2013;Zhang et al, 2015). Transcription factor genes GhABF2 (a bZIP transcription factor), AtEDT1/HDG11 (homeodomain-START transcription factor), AtRAV (related to ABA insensitive3/viviparous1), rice (Oryza sativa L.) NAC (a transcription factor), and AtSAP5 (a zinc-finger protein) have been introduced into cotton to increase drought tolerance (Hozain et al, 2012;Liu et al, 2014;Mittal et al, 2015;Liang et al, 2016;Yu et al, 2016).…”
Section: Overexpression Of Aldh21 From Syntrichia Caninervis Moss In mentioning
confidence: 99%